Microbiological survey of field‐grown and retail lettuce in Beijing. Issue 4 (15th May 2018) - Gao, Xiuzhi; Liu, Yiqian; Chang, Qing; Zhang, Zihao; Guo, Xu; Yi, Xinxin
Abstract: About 108 retail and 101 field‐grown lettuce samples from across Beijing were examined. These samples were analyzed for their aerobic plate counts, coliform counts, fecal flora counts, and presence of pathogenic bacteria. Samples included retail leaf ( n = 56), retail head ( n = 52), field‐grown leaf ( n = 54), and field‐grown head lettuce ( n = 47). The number of aerobic colonies of retail leaf lettuce was significantly higher than that of retail head lettuce throughout the year, with the exception of December. The means of retail leaf lettuce aerobic plate counts varied from 4.87 to 7.03 log10 cfu/g. For retail head lettuce, the mean count of aerobic microbiological populations varied from 4.33 to 6.33 log10 cfu/g. The aerobic microbiological populations of field‐grown lettuce were lower than those of retail lettuce in the same month. The mean count of field‐grown head lettuce was 5.53 log10 cfu/g. The mean count of retail head lettuce was 5.92 log10 cfu/g. The mean of the coliform counts ranged from <0.47 to 2.85 log10 cfu/g. Leaf and retail lettuce had significantly higher coliform, fecal flora, and Escherichia coli counts than head and field‐grown lettuce. The detection rate of E. coli was directly proportional to that of fecal flora. No E. coli O157:H7 or Salmonella spp. were detected in these lettuce samples. Practical applications: It is generally agreed that microbial contamination of lettuce will arise if there is improper operation in the process of its storage, transportation, and shelves sale. As lettuce is usually eaten raw, microbes can cause people to suffer from illnesses. Therefore, it is of critical importance to monitor the presence of microbes closely. In this study, the number of aerobic plate count in lettuce from different sources was examined. It was found that freshly picked lettuce had fewer microorganisms than retail lettuce had; lettuce harvested in low‐temperature seasons has fewer microorganisms than that in hot seasons. The suggestion is that cold chain transport is the best way for lettuce transportation, especially in summer and aseptic packaging is helpful to reduce contact pollution.